Stressors, coping, and resources needed during the COVID-19 pandemic in a sample of perinatal women - Celestina Barbosa-Leiker; Crystal Lederhos Smith; Erica J. Crespi; Olivia Brooks; Ekaterina Burduli; Samantha Ranjo; Cara L. Carty; Luciana E. Hebert; Sara F. Waters; Maria A. Gartstein (BMC, 2021)
Abstract Background Psychological stress and coping experienced during pregnancy can have important effects on maternal and infant health, which can also vary by race, ethnicity, and socioeconomic status. Therefore, we assessed stressors, coping behaviors, and resources needed in relation to the COVID-19 pandemic in a sample of 162 perinatal (125 pregnant and 37 postpartum) women in the United States. Methods A mixed-methods study captured quantitative responses regarding stressors and coping, along with qualitative responses to open-ended questions regarding stress and resources needed during the COVID-19 pandemic. Logistic and linear regression models were used to analyze differences between pregnant and postpartum participants, as well as differences across key demographic variables. Qualitative content analysis was used to analyze open-ended questions. Results During the COVID-pandemic, food scarcity and shelter-in-place restrictions made it difficult for pregnant women to find healthy foods. Participants also reported missing prenatal appointments, though many reported using telemedicine to obtain these services. Financial issues were prevalent in our sample and participants had difficulty obtaining childcare. After controlling for demographic variables, pregnant women were less likely to engage in healthy stress-coping behaviors than postpartum women. Lastly, we were able to detect signals of increased stressors induced by the COVID-19 pandemic, and less social support, in perinatal women of racial and ethnic minority, and lower-income status. Qualitative results support our survey findings as participants expressed concerns about their baby contracting COVID-19 while in the hospital, significant others missing the delivery or key obstetric appointments, and wanting support from friends, family, and birthing classes. Financial resources, COVID-19 information and research as it relates to maternal-infant health outcomes, access to safe healthcare, and access to baby supplies (formula, diapers, etc.) emerged as the primary resources needed by participants. Conclusions To better support perinatal women's mental health during the COVID-19 pandemic, healthcare providers should engage in conversations regarding access to resources needed to care for newborns, refer patients to counseling services (which can be delivered online/via telephone) and virtual support groups, and consistently screen pregnant women for stressors.